Geographic-inquiry on virtual environment mobile application to support fieldwork based on blended learning - Dwi Angga Oktavianto; Sugeng Utaya; Sumarmi Sumarmi; Didik Taryana (International Journal of Evaluation and Research in Education (IJERE), 2024)
Implementing geography learning using the blended learning model is challenging for most geography teachers because this subject is ‘hands-on’ and needs to be learned directly in a real environment using fieldwork. This study aimed to test the pedagogical effectiveness of the geographic-inquiry on virtual environment (GIVE) application in supporting fieldwork based on blended learning to improve students’ geographical thinking. This study used a quasi-experimental method involving 216 high school students from three schools. The paired sample t-test (Sig. 2-tailed 0.000) shows that GIVE has a pedagogical influence on students’ geographical thinking. GIVE also offers a big effect size (Cohen’s d=1.37). The technology and the right smartphone application can help develop a virtual environment close to a real one, so fieldwork and hands-on learning activities can be carried out in blended learning; this helps to increase the quality of geography learning.